2020 Parliamentary Elections in Online News Dailies: Do the Media Tend to Criticize the Ruling Party More - Danieliūtė, Iveta (Žurnalistikos tyrimai, 2023)
Voters tend to criticise and punish the ruling party for mistakes made during the term of office and therefore never vote for the same party twice in a row. However, there are no studies on whether the ruling party receives more criticism in the media during election periods.The article focuses on the portrayal of the opposing political parties – the Lithuanian Peasant and Green Union and the Homeland Union – Lithuanian Christian Democrats – in online news dailies during the 2020 parliamentary elections.The study shows that the media publishes more negative news about the ruling party, but that the communication strategy chosen by the politicians themselves also contributes to this. A link can also be found between the presentation of parties in the media and the final results of the parliamentary elections.
Keywords: politicians; party; media; parliamentary election